Numerical Investigation on Three-fluid Heat Exchanger for Hybrid Energy Source Heat Pumps. (May 2017) - Zhang, Weijia; Shao, Shuangquan; Zhang, Hainan; Tian, Changqing
Abstract: Hybrid energy source heat pump system is one of the best solutions to achieve efficient and stable utilization of renewable energies such as solar energy, geothermal energy, etc. The Three-fluid heat exchanger can realize heat transfer from the refrigerant to the outside air and the inside water simultaneously or independently, which will keep the refrigerant well distributed under difference working modes. The simulation model is built and validated for performance analysis of the three fluid heat exchanger based on Matlab and REFPROP. Three heat exchangers with different flow path designs are investigated for the heat transfer and pressure loss. The results show that the heat exchanger can give better performance by optimization of heat transfer coefficient and the pressure loss. Moreover, the influence on the heat exchanger from the variation of the air flow speed, air temperature, water flow speed and water temperature are also been analyzed.